Intangible Assets – An Open Issue - Cristina-Ionela Fadur (CES Working Papers, 2011)
We live in an ever more competitive, globalized world, in continuous technological evolution. Optimal resource management implies detailed knowledge on the value of intangible assets. In the present article, we aim to analyze the issue of intangible assets from the perspective of the Spanish accounting system, in order to identify the similarities and differences between it and the Romanian accounting system. The purpose of our approach is to complete the stage of knowledge concerning intangible capital – the hidden fortune of the new economy.
Keywords: M41; 330; intangible assets; intellectual capital; Centro Europeo de Empresas e Innovación de Navarra; El Instituto de Análisis de Intangibles; IAS 38 Romania